The Impact of Distance Learning Policies on Student Achievement in Elementary Schools during the COVID-19 Pandemic - Sulmiah (Celebes Journal of Elementary Education, 2023)
The COVID-19 pandemic has forced a rapid transition from face-to-face learning to Distance Learning (DL), posing significant challenges in elementary education, which plays a crucial role in the academic and social development of students. This study aims to examine the impact of DL on student learning achievements, focusing on factors that affect its effectiveness. The methodology used is a Systematic Literature Review (SLR), gathering data from 28 nationally and internationally accredited journals. The findings show that student learning achievements have variably decreased, influenced by technology accessibility, digital readiness of educators and students, and environmental support. Consequently, this study recommends the importance of enhancing digital infrastructure, continuous training for teachers, and inclusive strategies that support all students without deepening educational disparities. These findings are expected to assist policymakers and educational practitioners in designing more effective interventions to support DL in the future.